A walk through the 20th century with Bill Moyers [videorecording] the democrat and the dictator - Moyers, Bill (Public Broadcasting Service, 1990)
Bill Moyers explores the differences of Franklin D. Roosevelt and Adolf Hitler and the similar circumstances they faced in their struggle to control the world events.